Tolerance and Persistence to Drugs: A Main Challenge in the Fight Against Mycobacterium tuberculosis - Boldrin, Francesca; Provvedi, Roberta; Cioetto Mazzabò, Laura; Segafreddo, Greta; Manganelli, Riccardo (Frontiers in Microbiology, 2020)
The treatment of tuberculosis is extremely long. One of the reasons why M. tuberculosis elimination from the organism takes so long, is that in particular environmental conditions it can become tolerant to drugs and/or develop persisters able to survive killing even from very high drug concentrations. Tolerance develops in response to a harsh environment exposure encountered by bacteria during infection, mainly due to the action of the immune system, whereas persistence results from the presence of heterogeneous bacterial populations with different degrees of drug sensitivity, and can be modulated by exposure to stress conditions. Here we review the actual knowledge on the stress response mechanisms enacted by M. tuberculosis during infection, which lead to increased drug tolerance or development of a highly drug-resistant subpopulation.